Between the United Provinces and the United Kingdom of Portugal, Brazil and Algarve: the officers of the Royal Spanish Army in the years prior to the Independence of Brazil (Revista de Estudios Brasileños, 2023)
The intention of this article is to contribute to the understanding of the process of degradation experienced by the “loyal fernandinos” and by the officers and soldiers of the Royal Spanish Army who were part of Spanish espionage, while organizing the enterprise of reconquest of the Río de la Plata. To address the issues raised, we opted for the reduction of the scale of observation and “relational analysis”, because it gives us the possibility of paying attention to the universe of actions and exchanges that were carried out. Two perspectives of analysis that will allow us to observe the disputes of factions that for different reasons were wearing out the network of alliances and loyalties to the Spanish Monarchy, made up of a diverse set of Spanish officials, merchants and military. I am interested in showing the role played by the Spanish legation in Rio de Janeiro as a reference for the defenders of monarchical legality, the climate of extreme tension that led to the independence of the United Provinces and Brazil and the interdependence between the Iberian monarchies.